Application and mechanism of Chinese herb medicine in the treatment of non-alcoholic fatty liver disease - Liu, Yuqiao; Fan, Yue; Liu, Jibin; Liu, Xiyang; Li, Xiuyan; Hu, Jingqing (Frontiers in Pharmacology, 2024)
Non-alcoholic fatty liver disease (NAFLD) is a chronic liver condition closely associated with metabolic syndrome, with its incidence rate continuously rising globally. Recent studies have shown that the development of NAFLD is associated with insulin resistance, lipid metabolism disorder, oxidative stress and endoplasmic reticulum stress. Therapeutic strategies for NAFLD include lifestyle modifications, pharmacological treatments, and emerging biological therapies; however, there is currently no specific drug to treat NAFLD. However Chinese herb medicine (CHM) has shown potential in the treatment of NAFLD due to its unique therapeutic concepts and methods for centuries in China. This review aims to summarize the pathogenesis of NAFLD and some CHMs that have been shown to have therapeutic effects on NAFLD, thus enriching the scientific connotation of TCM theories and facilitating the exploration of TCM in the treatment of NAFLD.